HUBUNGAN PRAKTIK MONEY POLITICS TERHADAP SIKAP PRAGMATIS PEMILIH PEMULA DALAM PEMILU 2024 - Priyono, Diani; Zuryani, Nazrina; Pramestisari, Nyoman Ayu Sukma (JURNAL ILMIAH SOSIOLOGI: SOROT, 2025)
This research analyses the relation between the practice of money politics and the pragmatic behaviour of first-time voters in elections. Money politics, which involves offerjng incentives, which is often considered an effective strategy to gain support. On the other hand, first-time voters, participating in elections for the first time, often face political decision they do not fully understand. Data shows that 53,2% of respondents expect to receive incentives for voting, reflecting a pragmatic behaviour that tends to emerge during decision-making processes. This research uses a survey method with respondents aged 17-22 years old, sampled from first-time voters who are students of the Faculty of Social and Political Sciences at Udayana University. The questionnaire was designed to measure the significance of the relation between money politics and pragmatic behaviours although the correlation is low. Validity and reliability tests show 52 statements are valid and reliable. A normality test confirms the data is normally distributed, while a heteroscedasticity test indicates homogeneous data. Simple linear regression analysis reveals an equation with a constant of 34,450 and variable X coefficient of 0.310, with an R Square value of 13,6%. The T-test results show that Ha are accepted and H0 are rejected, proving that money politics could encourage pragmatic behaviour among first-time voters, although it’s influence are relatively low. This has the potential to undermine the quality pf democracy and electoral integrity. Therefore, efforts are needed to enhance political education for first-time voters to mitigate the negative impacts of money politics and foster more rational and critical political awareness. Keywords: money politics, pragmatic behaviour, first-time voters, election